Analisis Efektivitas Pengendalian Piutang Pada Koperasi Wanita “Sedap Malam” Desa Sidomulyo Kecamatan Purwoasri Tahun 2019-2023 - Muwahhidah, Zulva; Winarko, Sigit Puji; Nurdiwaty, Diah (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
Cooperatives in carrying out their activities to achieve the set goals must carry out control. The control that is implemented must be able to provide benefits, in this case it is able to increase the effectiveness and efficiency of cooperative operations. This study aims to analyze the control of receivables in the Women's Cooperative in Sidomulyo Village, Purwoasri District, Kediri Regency, during the period 2019 to 2023. This study uses a descriptive quantitative approach. The data analyzed includes the cooperative's financial statements, which are collected through interviews, observations, and documentation. The analysis technique used is to calculate the Receivable Turnover (RTO) ratio, and the Average Collection Period (ACP). The results of this study show that the control of receivables in the Women's Cooperative can be said to be effective. In the Receivable Turnover (RTO) ratio from 2019 to 2023, the receivables turnover rate can be said to be effective. In the Average Collection Period (ACP) from 2019 to 2023, it can be said to be effective.